2014
DOI: 10.4142/jvs.2014.15.4.485
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine protects against cadmium-induced oxidative stress in rat hepatocytes

Abstract: Cadmium (Cd) is a well-known hepatotoxic environmental pollutant. We used rat hepatocytes as a model to study oxidative damage induced by Cd, effects on the antioxidant systems, and the role of N-acetylcysteine (NAC) in protecting cells against Cd toxicity. Hepatocytes were incubated for 12 and 24 h with Cd (2.5, 5, 10 µM). Results showed that Cd can induce cytotoxicity: 10 µM resulted in 36.2% mortality after 12 h and 47.8% after 24 h. Lactate dehydrogenase, aspartate aminotransferase, and alanine aminotransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 36 publications
3
17
1
Order By: Relevance
“…There was significant increase in lipid oxidation byproduct, MDA level. This was the same as found by different research [25,26] in the pituitary gland and on other tissues [27][28][29].…”
Section: Discussionsupporting
confidence: 75%
“…There was significant increase in lipid oxidation byproduct, MDA level. This was the same as found by different research [25,26] in the pituitary gland and on other tissues [27][28][29].…”
Section: Discussionsupporting
confidence: 75%
“…It has been used as a mucolytic agent as well as an antioxidant in various clinical applications for more than 30 years (Cotgreave, 1997;Radomska-Lesniewska and Skopinski, 2012). The antioxidant role of NAC in reducing Cd toxicity was extensively studied in various cell lines and animal models (Odewumi et al, 2011;Luo et al, 2013;Wang et al, 2014). However, very few studies were reported on the immunomodulatory effect of NAC in reducing Cd toxicity in liver cells (Dong et al, 1998;Souza et al, 2004) and so far, no study was reported in lung cells.…”
Section: Introductionmentioning
confidence: 99%
“…The protective effects of NAC are evident in chronic diseases where decreased GSH or oxidative stress such as NASH occur (Ronis et al, 2005). NAC, as a source of sulfhydryl groups, stimulates GSH synthesis, enhances GSH-S-transferase (GST) activity and acts as a scavenger of free radicals, thus getting rid of ROS (Wang et al, 2014). It was selected in the current study as a representative of synthetic antioxidants, as it was welldocumented as a safe beneficial agent in a variety of pathologies (Rushworth & Megson, 2014).…”
Section: Introductionmentioning
confidence: 99%